PROFESSIONAL TEACHER TRAINING BASED ON SOCIAL PARTNERSHIP - Andrey V. Leifa; Yuriy P. Sergienko (Высшее образование в России)
The article highlights the development of mutually beneficial system of long-term and constructive cooperation between the University and social partners represented by potential employers such as secondary vocational, higher educational institutions, skills raising and retraining centres, governments and other organizations, in order to consolidate efforts for effective training of future teachers and sustainable development of pedagogical education in the region.